Implementation of Islamic Education in Strengthening Religious Moderation in Muslim Minority Areas: A Review of Albert Bandura’s Social Cognitive Theory - Rochmah, Ulifah Azwarani; Asrori, Mohammad; Masruri, M. Hadi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The complex dynamics of inter-religious relations have caused several problems in Muslim minority areas. One solution that is often echoed is religious moderation, which can be strengthened through Islamic education. In understanding it, Albert Bandura’s social cognitive theory is relevant, which has several concepts, namely modeling (imitation), self-efficacy (self-confidence) and reciprocal determinism (reciprocal interaction). This study aims to understand the implementation of Islamic education in strengthening religious moderation in the Christian Village of Suwaru in terms of Albert Bandura’s social cognitive theory. This research method uses a qualitative descriptive approach with a multi-case study type of research. The results of this study indicate that the religious moderation of the Muslim community of Suwaru is strengthened by the internalization of the values of religious moderation and moderate attitudes reflected in the implementation of Islamic education in the village. The contribution of Islamic education in strengthening the religious moderation of the Muslim community of Suwaru is shown by the role of religious figures who are role models for the community, as well as Islamic education that can increase self-confidence to maintain Islamic identity, as well as Muslim individuals, moderate behavior and the environment of Suwaru Village that influence each other. Some of these things are in line with the concepts of modeling, self-efficacy and reciprocal determinism in Albert Bandura’s social cognitive theory.